2012
DOI: 10.1002/bjs.8781
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of ultrasound-guided foam sclerotherapy versus surgery for the incompetent great saphenous vein

Abstract: At 2-year follow-up, UGFS was not inferior to surgery when reflux associated with venous symptoms was the clinical outcome of interest. UGFS has the potential to be a cost-effective approach to a common health problem. Registration numbers: NCT01103258 (http://www.clinicaltrials.gov) and NTR654 (http://www.trialregister.nl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 29 publications
5
89
1
5
Order By: Relevance
“…Twelve of the 34 included trials failed adequately to report methods of either randomisation or allocation concealment, or reported inadequate methods. [77][78][79][80]83,98,101,114,117,[120][121][122] Two further trials reported adequate randomisation but inadequate allocation concealment. 97,100 These studies, as reported, therefore had a high risk of selection bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve of the 34 included trials failed adequately to report methods of either randomisation or allocation concealment, or reported inadequate methods. [77][78][79][80]83,98,101,114,117,[120][121][122] Two further trials reported adequate randomisation but inadequate allocation concealment. 97,100 These studies, as reported, therefore had a high risk of selection bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…97,100 These studies, as reported, therefore had a high risk of selection bias. Thirteen studies either clearly failed to conduct an intention-to-treat analysis or left it unclear whether or not they had done so, and so were categorised as not clearly conducting such an analysis; 42,53,55,77,79,80,88,91,102,114,117,122,124 six of these also failed to report adequate methods of randomisation and allocation concealment, 77,79,80,114,117,122 all but one of which were abstracts only. 114 Two further key criteria were assessed that had the greatest potential to confound the results of this report: the non-comparability of groups at baseline and non-identical care programmes post intervention.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no limitations to using the technique after relapses, since in cases of recanalization the same patients can be treated again with the same method. 10 Polidocanol, in the form of foam, is the agent generally used in this type of treatment and it is painless and has a low incidence of allergic reactions. Treatment success rates have been reported by Gonzalez-Zeh et al,…”
Section: Introductionmentioning
confidence: 99%